Improving Children's Listening Ability Through Group A Puppet Play Media At TK Ar Raudhah SSMM - Melinda Puspita Sari Jaya; Ummiyati Ummiyati (Journal on Education, 2023)
This study aims to find out how wayang plays can improve the listening skills of group A children in TK AR RAUDHAH SSMM. The problem that researchers encountered in this study was the ability to listen to children who had not yet developed. This type of research is classroom action research (PTK). Data collection techniques for this research are observation, interviews, and documentation. The results of the study concluded that the average increase in the level of achievement of the development of the listening ability of group A children from pre-cycle to cycle I and to cycle II was that in the pre-cycle the score was 21.45 in the undeveloped category, then in cycle I with a score of 31, 45 with the category starting to develop while in cycle II with a score of 41.45 with the category developing according to expectations this shows that the pre-cycle results increased in cycle I then increased again in cycle II where it increased by 10. So it was concluded at the end of cycle II, the research is said to be successful because the success criteria have been achieved according to the agreement of the researcher and the collaborator